Synergistic effects of ischemic preconditioning and immediate post‐conditioning in the protection against ischemia/reperfusion injury in rabbit submandibular glands. (13th July 2018) - Zhang, Si‐en; Wen, Shi‐Hong; Su, Yu‐xiong; Zheng, Guang‐sen; Wang, Di‐kan; Liang, Yu‐jie; Liao, Gui‐qing
Abstract : Submandibular gland autotransplantation is an effective approach for treating severe keratoconjunctivitis sicca. However, ischemia/reperfusion (I/R) injury, which inevitably occurs during transplantation, is involved in the hypofunction and structural damage that occur early after transplantation. Therefore, it is critical to identify effective strategies to ameliorate I/R injury in submandibular glands. In this study, we investigated the ability of immediate post‐conditioning combined with ischemic preconditioning to attenuate I/R injury. We observed that after I/R injury, the level of reactive oxygen species was increased, inflammatory response was strengthened, and severe apoptosis had occurred. In addition, the salivary flow rate was greatly decreased. However, the pathogenesis of I/R injury was significantly ameliorated by ischemia post‐conditioning or ischemia preconditioning treatments. In addition, the combination of ischemia preconditioning and post‐conditioning achieved synergistic protective effects against I/R injury compared with ischemia preconditioning or ischemia post‐conditioning alone. The secretion function was restored in the combination group. Furthermore, the combination treatment involved the same mechanisms of ischemia preconditioning or ischemia post‐conditioning, including suppression of the inflammatory reaction and neutrophil accumulation, attenuation of oxidation stress, and inhibition of apoptosis. In conclusion, the combination of ischemia preconditioning and ischemia post‐conditioning treatment is a simple and effective approach for treating I/R injury in submandibular glands.